2003
DOI: 10.1074/jbc.m300905200
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of γ-Secretase

Abstract: Alzheimer's disease is characterized by formation of neurofibrillary tangles and amyloid plaques in the regions of the central nervous system that are involved in learning and memory (1). It is believed that accumulation of A␤ 1 in plaques or as soluble aggregates initiates a pathological cascade leading to synaptic dysfunction and neuronal toxicity, with neurodegeneration and dementia as the final outcome (1, 2). Therefore, strategies to reduce the level of brain A␤ are being aggressively pursued as an approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
44
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 37 publications
6
44
1
Order By: Relevance
“…(31,33). Furthermore, we showed that one of these non-transition state inhibitors, BMS-433796, exhibited noncompetitive displacement of [ 3 H]L-685,458 from SPP, suggesting a distinct binding site, which is potentially equivalent to the allosteric inhibitor binding site proposed for ␥-secretase (17,18). In addition, we found that the NSAID sulindac sulfide could displace the radioligand [ 3 H]L-685,458 from SPP at high concentrations, consistent with its reported modulation of SPP enzyme activity (34).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…(31,33). Furthermore, we showed that one of these non-transition state inhibitors, BMS-433796, exhibited noncompetitive displacement of [ 3 H]L-685,458 from SPP, suggesting a distinct binding site, which is potentially equivalent to the allosteric inhibitor binding site proposed for ␥-secretase (17,18). In addition, we found that the NSAID sulindac sulfide could displace the radioligand [ 3 H]L-685,458 from SPP at high concentrations, consistent with its reported modulation of SPP enzyme activity (34).…”
Section: Discussionmentioning
confidence: 87%
“…If so, the presence of SPP might account for the incomplete displacement of [ 3 H]L-685,458 observed for selective ␥-secretase inhibitors (18), thus calling into question the conclusion that the catalytic active site and the allosteric binding site are present in a 2:1 molar ratio (18). Furthermore, it seems likely that earlier studies of this radioligand in whole cell extracts may have detected predominantly SPP binding rather than ␥-secretase binding (17,37 From the drug discovery perspective, similar pharmacology between ␥-secretase and SPP suggests the potential for off-target liabilities. Additional studies would be needed to understand to what extent inhibitor binding affects enzyme function in vivo and to determine what consequences, if any, would arise from dosing a nonselective drug.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…First, these cleavages may be catalyzed by two enzymes, and second, these cleavages may be catalyzed by one enzyme that has two inhibitor binding sites, one for the transition state analogs, such as L-685,458, and the other for the nontransition state inhibitors, such as compound E, as suggested by a recent inhibitor binding kinetic study (23). The sequential relationship of these cleavages and specifically the finding that ␥-cleavage is dependent on ⑀-and -cleavages occurring first, suggest that ␥-, -, and ⑀-cleavages are catalyzed by a single enzyme.…”
Section: Discussionmentioning
confidence: 99%